PENGARUH LOKASI, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA KOPERASI SYARIAH MAWAR LAMONGAN - Rifky Ardhana Kisno Saputra; ali muhajir (TRANSFORMASI, 2022)
The study aims to determine the effec of location, promotion and services quality on customer satisfaction on the Cooperation Of Shariah Mawar Lamongan on Jl. Raya Simo Sungelebak, Karanggeneng, Lamongan Regency. This research is a survey with quantitave research. The population in this study were consumers Cooperation Of Shariah Mawar Lamongan. Sampling uses a purposive sampling technique and obtains a sample of 100 respondents using the Slovin formula. Data collection techniques using interviews and questionnaires. Analysis of the data used is validity test, reliability test, multiple linear regression analysis, classic assumption test, test coefficient of determination R2 and hypotesis testing through t test which is used to obtain location, promotion, and services quality partially on the Cooperation Of Shariah Mawar Lamongan.From the analysis results obtained t test results of the location variable t arithmetic = 2,769 > t table = 1.660 which determines the location agreed on the customer satisfaction. Variable promotion quality tcount = 1,991 > ttable = 1,660 which states the quality of the promotion against the customer satisfaction, and the services quality variable tcount = 3,970 > ttable = 1.660 that supports the services quality of the customer satisfaction. While R square of 0,727 shows that 72,7% of Customer Satisfaction variables are influenced by location, promotion and service quality. While the remaining 27,3% is influenced by other variables not examined.Keywords: Location, Promotion, Service quality, and Customer satisfaction.